IMPROVING STUDENTS’ READING COMPREHENSION THROUGH YOUTUBE AT GRADE VII OF SMPN 3 BUKIT BATU - Lismameriati Hutagaol (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Learning during the pandemic that supports 21st century learning uses online learning and media in the form of YouTube which has been prepared by the teacher in advance. The aim of this research was to improve students’ reading comprehension at grade VII of SMPN 3 Bukit Batu. This research used classroom action research conducted in two cycles, consisting of two lessons per cycle, involving a total of 27 students. The results of the research before the action showed an average score of 65.81, with 13 students completing the KKM and classical completeness of 48%. In the first cycle, learning was carried out using YouTube learning media, resulting in an average score of 70.2, with 20 students completing the KKM and classical completeness reaching 74.1%. Meanwhile, in the second cycle, an average score of 83.5 was obtained, with 26 students completing the KKM and classical completeness reaching 96.3%. The results of teacher observations indicated that the average cumulative score of learning observation activities in the first cycle was 66.7 and increased to 91.7 in the second cycle. Thus, it was concluded that the use of YouTube media was able to improve students’ reading comprehension.